Precise deployment scheme of 10G PON based on different scenarios - Yin LIN; Xiaoxia QIN; Guodong WANG; Shutian WEI (Dianxin kexue, 2021)
At present, with the rapid development of gigabit broadband users and gigabit applications, each communication operation has begun to accelerate the construction of gigabit optical network.However, in the upgrading process of 10G PON, two difficulties have gradually emerged, namely, high equipment cost and high complexity of network construction.Three models was established, including GPON gigabit user carrying capacity measurement model, investment benefit analysis model of gigabit network construction and gigabit value community identification model, to simulate and calculate the best 10G PON port deployment scenario of a mobile company, so as to realize the precise deployment of 10G PON port and support the development of gigabit broadband service efficiently.At the same time, the three models were also applicable to any communication operators in any region.The corresponding 10G PON network deployment scenarios can be simulated and output only by inputting the current PON network data and the current community data.